The Relationship between Situational Inhibitors and Informal Learning amongst Accountants - Abdul Wahab, Muhammad Syahir; Selamat, Mohamad Hisyam; Saad, Ram Al Jaffri; Mat Samsudin, Mohd Amir (2017)
The objective of this research was to examine the relationship between situational inhibitors and informal learning activities amongst 260 chartered accountants in public accounting firms across Malaysia.The data of the study was collected through mail survey approach and analysed using correlation analysis.The findings indicated that lack of time and lack of support from others inhibited the accountants’ informal workplace learning activities. These findings have implications for theory, practice and research of informal learning amongst accountants.